2020
DOI: 10.1111/pedi.12985
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diagnosis of maturity‐onset diabetes of the young in a cohort of Chinese children

Abstract: Objective: The purpose of this study was to investigate the molecular basis of maturity-onset diabetes of the young (MODY) by whole-exome sequencing (WES) and estimate the frequency and describe the clinical characteristics of MODY in southern China. Methods: Genetic analysis was performed in 42 patients with MODY aged 1 month to 18 years among a cohort of 759 patients with diabetes, identified with the following four clinical criteria: age of diagnosis ≤18 years; negative pancreatic autoantibodies; family his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 49 publications
(53 reference statements)
0
10
0
Order By: Relevance
“…Finally, due to the technology used for genetic investigations, some gene variations characterized by large gene deletions may have been overlooked. This group of large genomic rearrangements, including 17q12 microdeletions, have been described in literature as responsible for the majority of cases of HNF1B-MODY, known as MODY 5 [46,47]…”
Section: Discussionmentioning
confidence: 99%
“…Finally, due to the technology used for genetic investigations, some gene variations characterized by large gene deletions may have been overlooked. This group of large genomic rearrangements, including 17q12 microdeletions, have been described in literature as responsible for the majority of cases of HNF1B-MODY, known as MODY 5 [46,47]…”
Section: Discussionmentioning
confidence: 99%
“…The study on Russian children with non-type 1 diabetes showed that the most prevalent MODY type was GCK, with only 18% of variants in other than known MODY genes. The studies from China reported that HNF4A MODY types were relatively less common as compared to Europeans[ 18 , 19 ]. A study from Korea also has a similar finding that common MODY types prevalent in Europe were not common there, but instead they found variants in three new genes, including the WFS1 gene[ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, monogenic diabetes, especially Maturity onset diabetes of the young (MODY), is an emerging type of diabetes lately in Chinese children and adolescents, which was commonly misdiagonised. 2 Third, pediatric diabetes is a lifelong disease with multiple tricky complications. Diabetic ketoacidosis (DKA) is the most serious cause of death in pediatric diabetes.…”
Section: Introductionmentioning
confidence: 99%